Prevention of alcohol consumption and transmission of human immunodeficiency virus: randomized clinical trial - Martha Dalila Mendez-Ruiz; Miguel Angel Villegas-Pantoja; Nohemí Selene Alarcón-Luna; Natalia Villegas; Rosina Cianelli; Nilda Peragallo-Montano
Abstract Objective: to know the effects of a nursing intervention to reduce alcohol use and risk factors for transmission of human immunodeficiency virus (HIV). Method: randomized single-blinded clinical trial performed by nurses with young women. The study included 66 participants in the intervention group and 66 participants in the control group. The instruments were the Alcohol Use Disorders Identification Test, the HIV Risk Behavior Knowledge and the Condom Use Self-efficacy Scale. Analysis of variance was used. Results: alcohol involvement decreased in the intervention group (F (1.119) = 50.28; p < 0.001; η2p = 0.297), while HIV knowledge (F (1.130) = 34.34; p < 0.001; η2p = 0.209) and condom use self-efficacy increased (F (1.129) = 27.20; p < 0.001; η2p = 0.174). In addition, less participants consumed alcohol in the past week compared to the control group (χ2 = 15.95; p < 0.001). Conclusion: the nursing intervention had positive effects, which could help young women stay away from alcohol use and the risk of sexually transmitted infections. NCT: 02405481.